Strand switching during rolling circle replication of plasmid-like DNA circles in the mitochondria of the higher plant Chenopodium album (L.). - Backert, Steffen (Plasmid, 2000)
The structure of sigma-like mitochondrial DNA molecules prepared from suspension cultured cells of Chenopodium album (L.) was studied by electron microscopy. These molecules were highly variable in size, ranging from about 1 to 104 kb, and had single- and double-stranded regions typical for rolling circle replicating intermediates. Partial denaturation studies confirmed that these structures constitute rolling circles. Close inspection of the circle-tail junctions of the replication fork at high magnification suggests that in circles with a double-stranded tail, both strands of the tail seem to be covalently attached to the circle in about 27% of the molecules. This observation can be explained by a phenomenon called strand switching or strand splippage during rolling circle replication, similar to a mechanism proposed for bacterial replicons or in vitro replicating constructs harboring bacteriophage T4 replication origins.